2023
DOI: 10.1021/acs.inorgchem.2c04471
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Robust Iridium(III) Complex-Based Photosensitizer for Boosting Hydrogen Evolution

Abstract: Developing a photosensitizer with high efficiency and long-term stability for photocatalytic hydrogen evolution is highly desirable yet remains a challenge. Herein, a novel Ir(III) complex-based photosensitizer (Ir3) bearing coumarin and triphenylamine groups is designed. Ir3 exhibits record activity and durability among reported transition metal complexes for photocatalytic hydrogen evolution, with a TON of 198,363 and a duration of 214 h. The excellent photocatalytic performance of Ir3 can be attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The DFT calculated energy gaps ( E gap , Table S7) between the highest occupied MO (HOMO) and LUMO also exhibited the same regularity. Such small E gap and low excitation energy level ESs with IL characterizations may suggest a favorable efficacy of electron excitation and transfer for not only PSs in the PDT , but also Ir­(III) photocatalysts in hydrogen evolution and CO 2 reduction …”
Section: Resultsmentioning
confidence: 99%
“…The DFT calculated energy gaps ( E gap , Table S7) between the highest occupied MO (HOMO) and LUMO also exhibited the same regularity. Such small E gap and low excitation energy level ESs with IL characterizations may suggest a favorable efficacy of electron excitation and transfer for not only PSs in the PDT , but also Ir­(III) photocatalysts in hydrogen evolution and CO 2 reduction …”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the structurally modified complexes only had a photocatalytic lifetime of 18 h. 60 We have previously reported the highest TON of 198 363 and a lifetime of 214 h by introducing coumarin and triphenylamine (TPA) groups into the iridium photosensitizer. 61 Moreover, the most effective method for enhancing photocatalytic stability is the introduction of large steric hindrance groups at the end of the auxiliary ligand. Park et al enhanced stability by introducing triphenylsilyl (TPS) in an auxiliary ligand, achieving a photocatalytic lifetime of 144 h. 62 In our previous work, Ir photosensitizers were loaded onto polypropylene films grafted with maleic anhydride to achieve extremely long photocatalytic lifetimes of 730 h and 652 h. Nevertheless, film loading decreased the hydrogen production activity by 39.1 mmol g −1 and 86.4 mmol g −1 respectively, indicating that excessive steric hindrance is not conducive to the photocatalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed a considerable expansion in the use of cyclometalated neutral and charged Ir(III) complexes as photosensitizers (photoredox catalysts) in a wide range of photochemical reactions. Such reactions involve photoinduced electron/energy transfer processes, which are of key importance for promoting photoredox catalysis and light-to-chemical energy conversion. Recent studies have revealed that coumarin 6 is a promising cyclometalating ligand that endows both cationic and anionic Ir(III) complexes with strong visible-light absorption ( ε ≈ 100,000 M –1 cm –1 at around 480 nm) and long-lived triplet excited states (τ ≈ 20 μs) for effective photocatalytic H 2 evolution. Nevertheless, these complexes gradually degrade during reactions involving inefficient photoredox cycles because the one-electron-reduction products generated by the reductive quenching of these complexes are unstable. , Such a drawback, which is typical of coumarin-based ionic Ir(III) complexes, motivated us to pursue new approaches that provide complementary durability in order to propel them to the forefront of artificial photosynthesis development.…”
mentioning
confidence: 99%